2010
DOI: 10.3991/ijim.v4i2.1167
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Mobile Learning Among Distance Education Students in Universiti Sains Malaysia

Abstract: This study was carried out in order to investigate whether mobile learning using Short Message Service (SMS) was a method of learning adopted by the students enrolled in the School of Distance Education, Universiti Sains Malaysia. As adult learners who are in vocation, time and isolation are the bane of self-study. Since all the students own a mobile device that can receive SMS, educational messages can be sent directly to their devices. This experimental study explored the impact of learner’s characteristic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
2
11
0
1
Order By: Relevance
“…Most of the students agreed on the fact that m-learning will encourage a sense of responsibility and independent learning thus increasing their confidence and make them more active and involved in creating knowledge. These results are in line with [Al-Fahad [21], 22,23]. In general, the study revealed the positive attitude towards the advantages of mlearning.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the students agreed on the fact that m-learning will encourage a sense of responsibility and independent learning thus increasing their confidence and make them more active and involved in creating knowledge. These results are in line with [Al-Fahad [21], 22,23]. In general, the study revealed the positive attitude towards the advantages of mlearning.…”
Section: Discussionsupporting
confidence: 81%
“…The existing challenges in mlearning from cultural perspectives covers in Malaysia: Lack of devices support for mlearning [22]; Inadequate of appropriate mlearning local culture content [32]; Lack of culture aspects in mlearning design content [3][8]; Lack of telecommunication wireless infrastructure in the rural areas [18] [19]. In addition, there are opportunities in mlearning from cultural perspectives in Malaysia: development for variety types of mlearning cultural content; support from government to create mlearning cultural content; students motivation and engagement with potential mlearning cultural content [3] [8].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is also the usage of short message services (SMS) which to a certain extent need a good service infrastructure for message delivery [18] [19]. Also, the availability context is referring to the users of the mobile learning technology [33].…”
Section: ) Accessibilitymentioning
confidence: 99%
“…O tablet, computador em forma de prancheta eletrônica com teclado virtual e tela sensível ao toque é a tecnologia mais implementada em instituições de ensino de diversas localidades no mundo dentre as tecnologias móveis presentes atualmente (MADAN, 2011;ISMAIL, 2010). De acordo com Madan (2011), é visto atualmente como a melhor forma de apresentar uma informação através de aplicativos de textos, imagens, vídeos e áudios.…”
Section: Introductionunclassified